Accounting Manipulation, Peer Pressure, and Internal Control - Gao, Pingyang; Zhang, Gaoqing (The Accounting Review, 2019)
ABSTRACT We study firms' investment in internal controls to reduce accounting manipulation. We first show that peer managers' manipulation decisions are strategic complements: one manager manipulates more if he believes that reports of peer firms are more likely to be manipulated. As a result, one firm's investment in internal controls has a positive externality on peer firms. It reduces its own manager's manipulation, which, in turn, mitigates the manipulation pressure on managers at peer firms. Firms do not internalize this positive externality and, thus, underinvest in their internal controls over financial reporting. The problem of underinvestment provides one justification for regulatory intervention in firms' internal controls choices. JEL Classifications: G18; M41; M48; K22.